DETERMINAN PERSEPSI MAHASISWA AKUNTANSI MENGENAI ETIKA ATAS TAX EVASION - Talita Ayu Sylviana; Santi Rahma Dewi (Behavioral Accounting Journal, 2020)
This research aims to examine the factors that influence perceptions about the ethics of tax evasion in accounting students. The population in this study were active students of Bachelor degree (S1) 2016 semester 8 of Accounting Studies Program at the Faculty of Business, Law and Social Sciences, Muhammadiyah University, Sidoarjo. This research uses quantitative methods. The sample in this study amounted to 150 semester 8 accounting students who were determined using the Purposive sampling method. The data of this study were sourced from questionnaires distributed to respondents and then analyzed with multiple linear regression analysis.The results showed that the fairness factor had a significant effect on the perception of ethics on tax evasion. Tax system factors have no significant effect on perceptions of ethics on tax evasion. Meanwhile, discrimination has a significant effect on perceptions of ethics on tax evasion.